Targeting Tax Enforcement Efforts on Larger Firms : A Necessary Distortion? - Bachas, Pierre (World Bank, Washington, DC, 2021)
To collect tax revenue and maximize the use of scarce enforcement capacity, some tax administrations focus their enforcement efforts disproportionately on large firms instead of enforcing taxes evenly on firms of all sizes: small, medium, or large. This Research & Policy Brief provides evidence that size-dependent tax enforcement is prevalent, especially in lower-income countries, leading to increasing effective tax rates as firms become larger. The Brief then quantifies the impact of this policy for aggregate economic production. It finds that the impacts are moderate (amounting to about a 1 percent decline in total factor productivity), and thus could be justified for tax authorities with limited resources, given documented tax revenue gains of stringent enforcement targeted to large firms.